2017
DOI: 10.1589/jpts.29.931
|View full text |Cite
|
Sign up to set email alerts
|

Static balance according to hip joint angle of unsupported leg during one-leg standing

Abstract: [Purpose] This study aimed to determine static balance according to hip joint angle of the unsupported leg during one-leg standing. [Subjects and Methods] Subjects included 45 healthy adult males and females in their 20s. During one-leg standing on the non-dominant leg, the position of the unsupported leg was classified according to hip joint angles of point angle was class. Static balance was then measured using a force plate with eyes open and closed. The total length, sway velocity, maximum deviation, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While maintaining postural stability depends on the vestibular system, proprioception receptors, and visual system, studies evaluating these three systems individually in balance tests have confirmed that the visual system is particularly crucial in influencing balance [ 34 ]. Cha et al showed that subjects’ center of gravity moved more when their eyes were closed than when they were open [ 35 ], whereas Rose [ 36 ] found a much larger center of gravity displacement when subjects stood one-legged with their eyes closed in comparison with that obtained in a stance with the eyes open. Static balance studies have also already shown comparable results.…”
Section: Methodsmentioning
confidence: 99%
“…While maintaining postural stability depends on the vestibular system, proprioception receptors, and visual system, studies evaluating these three systems individually in balance tests have confirmed that the visual system is particularly crucial in influencing balance [ 34 ]. Cha et al showed that subjects’ center of gravity moved more when their eyes were closed than when they were open [ 35 ], whereas Rose [ 36 ] found a much larger center of gravity displacement when subjects stood one-legged with their eyes closed in comparison with that obtained in a stance with the eyes open. Static balance studies have also already shown comparable results.…”
Section: Methodsmentioning
confidence: 99%
“…Factors such as age, body mass index (BMI), and muscle strength affect gait speed 11 . Moreover, 1-leg standing time (OLST) and the functional reach test are known as good indicators of balance function and are useful as tools for evaluating lower-limb function 12,13 . With regard to lower-limb alignment after THA, postoperative leg-length discrepancy and several offset differences are related to gait 14 .…”
mentioning
confidence: 99%
“…9 Furthermore, balance skills, including one-leg standing time (OLST), are known as good indicators of walking ability and are important for evaluating lower limb ability. 10 However, previous reports have not examined whether preoperative affected side or non-affected side performance was more important for postoperative walking ability. Only Ohmori et al 11 reported that preoperative non-affected side ability affected walking speed 1 year after THA, but it is unclear whether non-affected side ability is also important in early postoperative walking independence.…”
Section: Introductionmentioning
confidence: 98%